2018
DOI: 10.1111/ced.13840
|View full text |Cite
|
Sign up to set email alerts
|

Ingenol mebutate for the treatment of anogenital condylomata acuminata

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…The recurrence rate was reported by 18% up to 12 months of follow-ups. 5 Despite the high incidence of complete resolution and low reported recurrence rates in the previous studies, in our series, initially, AGWs were completely cleared in 10 (66%) patients while 4 (40%) patients experienced the recurrence within a 3-month followup meaning that the 3-month complete clearance of AGWs was achieved in only six (40%) cases. It should be noted that the patient population was mainly consisted of the refractory cases in this trial possibly explaining the observed lower clearance rate and a high recurrence rate in this study.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…The recurrence rate was reported by 18% up to 12 months of follow-ups. 5 Despite the high incidence of complete resolution and low reported recurrence rates in the previous studies, in our series, initially, AGWs were completely cleared in 10 (66%) patients while 4 (40%) patients experienced the recurrence within a 3-month followup meaning that the 3-month complete clearance of AGWs was achieved in only six (40%) cases. It should be noted that the patient population was mainly consisted of the refractory cases in this trial possibly explaining the observed lower clearance rate and a high recurrence rate in this study.…”
Section: Discussioncontrasting
confidence: 71%
“…In another study, 11 of 15 (73.3%) patients with AGWs showed the complete clearance after application of the IM gel (0.15% or 0.05%). The recurrence rate was reported by 18% up to 12 months of follow‐ups 5 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…AGW are benign epithelial tumors caused by an infection with certain types of human papillomavirus (HPV) [ 4 ]. Many individual case reports, smaller case series, and initial pilot studies have shown, that IM gel application effectively and quickly removes AGW [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In most cases, a single application of the gel was sufficient to ablate the warts within 24 h. After 8 h, the treated warts showed clinical signs of necrosis and peeled off within the next 24 h. Some patients felt severe pain at the treatment site, which peaked after 8 h and quickly ameliorated over the next half day.…”
Section: Introductionmentioning
confidence: 99%